Optimizing IT Service Strategies: A Performance Assessment through ITIL V3 in PT XYZ IT Operations Division - Sholekha, Kharisma Putri; Akhmarullah, Nauval Dwi Yuzhak; Tarwoto, Tarwoto; Ramadhan, Andra Dwi; Setiawan, Hasan; Prasetyo, Ilham Cipto; Hermawan, Sabana Nur Rizki (International Journal of Informatics and Information Systems, 2023)
In building a system in an IT organisation, it is necessary to have the support of an IT Service that is able to adapt to business needs continuously. IT services mainly run and grow from within the company. The Information Technology Infrastructure Library (ITIL) is the most commonly adopted framework for IT service management. Starting the use of ITIL can be done by identifying areas that can be developed and measuring the current situation. This will help to know the desired future state and be the basis for finding solutions to improve performance based on ITIL. Maturity level measurement is one of the commonly used methods to define the current situation. The purpose of this research is to understand how well a team from a small company is doing business using maturity levels. ITIL's seven-step improvement process was chosen and adapted as a guide to carry out the entire research. The research was conducted by conducting maturity assessments and interviews at a small IT services company. Measurements were carried out twice. At first, it serves to determine the condition before measurement and improvement. Research in the IT Operations division of XYZ revealed that ITIL implementation can increase maturity levels in accordance with company management objectives. In the end, the implications of this research will provide company management with factors and solutions to improve performance based on ITIL implementation.